2008
DOI: 10.1016/j.pec.2008.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of health behavior theories with self-efficacy among insufficiently active hypertensive African–American women

Abstract: Objective-While self-efficacy plays an important role in physical activity, relatively little research has examined this construct in minorities. This study identified theoretical correlates associated with self-efficacy amongst insufficiently active, hypertensive Black women.Methods-Correlates of self-efficacy to: (1) overcoming barriers to physical activity; (2) making time for activity; and (3) "sticking with" physical activity were studied.Results-Sixty-one women (M = 50.48 ± 4.2 years) participated. We ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 71 publications
(39 reference statements)
3
36
0
1
Order By: Relevance
“…[16] The self-efficacy framework related to DM has been applied in various education programs. [17] These studies demonstrated that self-efficacy correlated with compliance to physical activity, [18] and diet regimen [19] and to be associated with more frequent self-monitoring of blood glucose [20] and glycemic control. [21] Conversely, low selfefficacy was associated with worse diabetes control.…”
Section: Introductionmentioning
confidence: 99%
“…[16] The self-efficacy framework related to DM has been applied in various education programs. [17] These studies demonstrated that self-efficacy correlated with compliance to physical activity, [18] and diet regimen [19] and to be associated with more frequent self-monitoring of blood glucose [20] and glycemic control. [21] Conversely, low selfefficacy was associated with worse diabetes control.…”
Section: Introductionmentioning
confidence: 99%
“…At the environmental level, barriers to healthy lifestyles include lack of access to exercise facilities at work or in the community, lack of bicycle and walking paths as well as high traffic and crime in urban settings that prevent access to safe walking areas. For individual African-Americans, overall perceived and real barriers to engage in exercise and healthy diets may outweigh perceived positive outcomes of total lifestyle changes, underscoring the importance of individual effective problem solving to reduce barriers and information to influence outcome [36,37]. …”
Section: Discussionmentioning
confidence: 99%
“…For individual African Americans, overall perceived and real barriers to engage in exercise and healthy diets may outweigh perceived positive outcomes of total lifestyle changes, underscoring the importance of individual effective problem solving to reduce barriers and information to influence outcome expectancies. 29,30 These important culturally relevant factors were incorporated into the nutrition and physical activity educational materials, which were provided to patients at each study visit.…”
Section: Discussionmentioning
confidence: 99%